Biodiesel production from heterotrophic microalgal oil - Miao, X.; Wu, Q.
The present study introduced an integrated method for the production of biodiesel from microalgal oil. Heterotrophic growth of Chlorella protothecoides resulted in the accumulation of high lipid content (55
Keywords: BIODIESEL; TRANSESTERIFICATION; MICROALGAL OIL; HETEROTROPHIC; CHLORELLA PROTOTHECOIDES; ACID CATALYST